Chiral separations of mandelic acid by HPLC using molecularly imprinted polymers - Hung, Chin-Yin; Huang, Han-Hung; Hwang, Ching-Chiang (Eclética Química, 2005)
Styrene is used in a variety of chemical industries. Environmental and occupational exposures to styrene occur predominantly through inhalation. The major metabolite of styrene is present in two enantiomeric forms, chiral R- and S- hydroxy-1-phenyl-acetic acid (R-and S-mandelic acid, MA). Thus, the concentration of MA, particularly of its enantiomers, has been used in urine tests to determine whether workers have been exposed to styrene. This study describes a method of analyzing mandelic acid using molecular imprinting techniques and HPLC detection to perform the separation of diastereoisomers of mandelic acid. The molecularly imprinted polymer (MIP) was prepared by non-covalent molecular imprinting using (+) MA, (-) MA or (+) phenylalanine, (-) phenylalanine as templates. Methacrylic acid (MAA) and ethylene glycol dimethacrylate (EGDMA) were copolymerized in the presence of the template molecules. The bulk polymerization was carried out at 4 o C under UV radiation. The resulting MIP was grounded into 25~441⁄4m particles, which were slurry packed into analytical columns. After the template molecules were removed, the MIP-packed columns were found to be effective for the chromatographic resolution of (±)-mandelic acid. This method is simpler and more convenient than other chromatographic methods.